TERRITORY, OPULATION, ETHNOSES, ND SECURITIZATION: ON THE ENDOGENOUS FACTORS OF SECURITY IN THE REGIONAL SYSTEMS OF THE CAUCASUS AND CENTRAL ASIA - EYVAZOV, Jannatkhan (CENTRAL ASIA AND THE CAUCASUS, 2007)
This is an attempt to assess the endogenous security factors of the regional political systems of the Caucasus and Central Asia in order to find out, in particular, how the region’s territorial-demographic and ethnic factors affect the basic perceptions of security, as well as the securitization1 processes occurring in this context. I do not claim to provide exhaustive answers here to all the questions relating to the problems I in end to investigate. At the same time, the specifics of the territorial, demographic, and ethnic structures, especially in the regions in which “modern states”2 predominate (Central Asia and the Caucasus belong precisely to this category), directly affect the perceptions of the threats and vulnerabilities created by the foreign political environment and domestic sub-national groups. This approach might clarify the reasons for the post-Soviet conflict dynamics in the Caucasus and Central Asia. This assessment is based on certain specific conceptual-categorial provisions calling for preliminary explanation. First, this article looks at the regional political systems of the Caucasus and Central Asia as Regional Security Complexes (RSC).3 Second, I do not intend to operate using the fairly limited traditional spatial political division of the Caucasus into two segments— the Northern and the Southern Caucasus. I am proceeding from a relatively recent, yet much more adequate structure (the Northern, Central, and Southern Caucasus) better suited to objectively reflect the region’s most important geopolitical and ethnocultural specifics.